Tranexamic Acid in the Management of Non-variceal Upper Gastrointestinal Bleeding - Reza, Muhammad; Nursyirwan, Saskia Aziza (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Non-variceal upper gastrointestinal bleeding (UGIB) is a common case of emergency in daily clinical practice with a fairly high mortality rate. The use of tranexamic acid, which has been recommended in managing trauma bleeding, may serve as an alternative pharmacological therapy to manage bleeding in non-variceal UGIB. This evidence-based case report aims to evaluate the impact of tranexamic acid on managing bleeding, risk of mortality, and thromboembolic event in non-variceal UGIB patients.Methods: A systematic literature search was conducted on 4 databases: CDSR, EMBASE, PubMed, and Scopus for meta-analyses. Studies were selected based on inclusion and exclusion criteria formulated a-priori with subsequent critical appraisal according to the OCEBM critical appraisal tools. Result: Meta analyses by Kamal, et al (2020) and Twum-Barimah, et al (2020) were included in our report. Kamal, et al shows no significant difference in mortality in tranexamic acid use compared to placebo (RR 0.84; 95%CI 0.63–1.11; I2=2%). Similarly, although Twum-Barimah reported tranexamic acid reduced risk of mortality compared to placebo (RR 0.45; 95%CI 0.23–0.88; p=0.02; I2 = 0%), none of the RCTs included shows significant result when observed individually. In addition, Kamal, et al also reported increased risk of vein thromboembolic events in high-dose tranexamic acid administration (RR 2.21; 95%CI 1.32–3.69; I2=0%) compared to low-dose administration, in UGIB patients.Conclusion: Tranexamic acid is not recommended to be used in managing bleeding in patients non-variceal UGIB patients and may increase the risk of thromboembolic event.